(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Transportation is a strategic sector of the EU’s economy and directly impacts the daily lives of all EU citizens. This industry is responsible for around 11 million jobs. It is vital for the integration of Europe, as interconnected and sustainable transport networks are necessary to complete and adequately function the European Single Market. Over the last few decades, passenger and freight transport volumes have grown, and they are expected to continue to do so, although at a slower pace. Most passenger and freight transport is through road transport, and this article focuses on regulating road transport and its compatibility with the objectives of the European Green Deal. The European Commission has put forth a set of propositions to align the EU's climate, energy, transport, and taxation policies to achieve a minimum reduction of 55% in net greenhouse gas emissions by 2030 compared to the levels recorded in 1990. One proposition is to reduce road transport pollution by increasing the percentage of electric vehicles operating in the road transport sector. This paper aims to introduce the concept of the electric road vehicle, analyse the objectives of the European Green Deal, and discuss Lithuanian policy actions regarding electric road vehicles and related infrastructure.